THE USE OF JUMBLED SUMMARY STRATEGY IN TEXT NARRATIVE TO IMPROVE THE STUDENTS’ ABILITY READING COMPREHENSION AT EIGHTH GRADE OF SMP NEGERI 10 MEDAN - Kartini Cahaya Septiana S; Fenty Debora Napitupulu; Yessy Octavianna (Sean Institute, 2023)
The purpose of this research is aimed to find out whether or not the use of jumbled summary strategy can improve reading comprehension of 8th grade students of SMP Negeri 10 Medan in narrative text. The thesis discusses the improvement reading comprehension using jumbled summary strategy. Since the purpose of this research to find out whether or not using jumbled summary strategy for the improvement reading comprehension, this research classified into action research with qualitative and quantitative approaches. There were two cycles used in this research. There are four steps each cycle, planning, action, observation, and reflection. The subjects of this research are 32 students in the eight grade of SMP Negeri 10 Medan. The data of this research were quantitative collected from the pre-test and post-test using 25 multiple choice questions. The qualitative data obtained from observation and field note. The result of this research is improvement reading comprehension using jumbled summary. According to the data that collected from cycle I dan cycle II the average is increased significantly from 48.5 to 69.83 that is good results even though they have not yet reached the indicator of 90% of students.